Web of Knowlege – an important tool for working with information on research - V. E. Vaskovsky (Библиосфера)
Database Web of Knowledge (WoK) is an essential instrument for work with information during scientific researches. Short information on technique to retrieve and analyze collected information is given. The possibilities of WoK are demonstrated on the analysis of topical basic and applied problem Personalized Medicine.